Five-year outcome after pelvic floor reconstructive surgery: evaluation using dynamic magnetic resonance imaging compared to clinical examination and quality-of-life questionnaire - Alt, Céline D.; Benner, Laura; Mokry, Theresa; Lenz, Florian; Hallscheidt, Peter; Sohn, Christof; Kauczor, Hans-Ulrich; Brocker, Kerstin A. (Acta radiologica, 2018)
Background Dynamic magnetic resonance imaging (dMRI) captures the entire pelvis during Valsalva maneuver and helps diagnosing pelvic floor changes after reconstructive surgery ...